A multilevel approach to energy options across EU: the role of supra-national governance, values and trust - Mouro, C.; Castro, P.; Kronberger, N.; Duarte, A. P. (International Review of Social Psychology / Revue Internationale de Psychology Sociale, 2013)
The European Union (EU) has in the last decades proposed several policies to promote sustainable forms of energy production. This topic brings together environmental concerns and technological innovation, two domains traditionally seen as opposite. To help understand how the publics mobilize for this debate, we examined the Science & Technology (S&T) and Public Understanding of Science (PUS) 2010 Eurobarometer resorting to a multi-level approach. We examined the role of cultural aspects, like worldviews and institutional trust, and country-level distinctions, namely the stage of accession to EU. Results show that egalitarians are more supportive of solar energy and less supportive of nuclear energy than hierarchics, although support for both technologies is (positively) predicted mainly by institutional trust. Active involvement in S&T and Environmental matters relies mostly on awareness about environmental problems, but is also related to believing technology will provide inexhaustible resources. At the contextual-level, newer EU member-states are less supportive of solar energy, more supportive of nuclear energy and less actively engaged in civic participation than older member-states. The findings highlight the intricate liaison between environmental and technological matters in the public debate about energy production and bring to the fore the relevance of legal innovation as determinant of value change.